COOKING CHARACTERIZATION OF ARROWROOT (Maranta arundinaceae) NOODLE IN VARIOUS ARENGA STARCH SUBSTITUTION [Karakteristik Pemasakan Mie Garut (Maranta arundinaceae) Pada Variasi Subtitusi Pati Aren] - Miftakhussolikhah, Miftakhussolikhah; Ariani, Dini; RNH, Ervika; Angwar, Mukhamad; Wardah, Wardah; Karlina, L Lola; Pranoto, Yudi (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Arrowroot (Maranta arundinaceae) tuber has traditionally been used by Indonesian people as a source of carbohydrate in their food diet. It will be likely more preservable and flexible when the tuber is processed into flour as an alternative raw food material. Arrowroot flour should be mixed with other material that have high amylose content for making noodles, thus the noodles have good quality almost same as commercial product. The objective of this study was to investigate the effect of arenga starch substitution on the arrowroot flour noodle qualities including appearance, cooking, textural and sensory properties. Noodle was made with five variation of arrowroot flour and arenga starch composition i.e. 0:100, 25:75, 50:50, 75:25, 100:0. Characterization of noodle qualities and hedonic test of noodle were analyzed. The results show that arrowroot flour substitution affects noodle qualities such as color, brittleness, cooking time, cooking loss, swelling index, expantion ratio, tensile strength, elongation and stickiness. Noodles that have characteristic nearest to commercial products and the most favored product by panelists was the mixture of arrowroot flour 25: arenga starch 75.